Hypoglycemic Effect of Moringa oliefera Lam. Seed Oil Extract and Royal Jelly Composite Mixture in Alloxan-Induced Diabetes in Male Albino Wistar Rats - Jr., Romulo R. Macadangdang; Orodio, Albert Lorenz T.; Calabio, Alison Green T.; Miciano, Kristine Bernardeen V.; Tan, Alexandrine Coleen L. (Asian Journal of Biological and Life Sciences)
Artificial diabetes was introduced to healthy male albino wistar rats to establish the hypoglycemic effect of the combined Moringa oleifera Lam. seed oil (MOSO) extract with royal jelly (RJ). Moringa oleifera Lam. seed oil was afforded via Soxhlet extraction with hexane and subsequent phytochemical analysis was performed revealing the presence of alkaloids and flavonoids. There were five treatment groups (pure MOSO, MOSO-10, MOSO-15, MOSO-20, and pure RJ) and a negative control group used in this study. The treatment with 20% loading (MOSO-20, Treatment D) of the seed oil extract in royal jelly was found to be the fastest to normalize the blood glucose levels in seven days, followed by Treatment E, Treatment C, Treatment B, and Treatment A. Analysis of variance and Tukey’s HSD post hoc analysis of data revealed that treatment groups had results which were significantly different (p < 0.05). Results of this research can be used to explore the synergistic effects of MOSO and RJ in the future.
Keywords: Antihyperglycemic; Blood glucose; Moringa oleifera; Royal Jelly